Influência de diferentes parâmetros em métodos de extração de compostos bioativos de mirtilo (Vaccinium ashei Reade) e atividade antioxidante e antimicrobiana - Piovesan, Natiéli (2016)
This study aimed to investigate the influence of different parameters (concentration of solvent, time, temperature and power) in extraction methods (focused microwave, conventional and ultrasound) bioactive compounds in blueberries, seeking higher yield of compounds biativos, antioxidant and antimicrobial activity of the extracts.The extracts were characterized regarding the phenolic compounds, flavonoid and anthocyanins content. The in vitro antioxidant activity was quantified by the methods of DPPH, ABTS, FRAP, and β-carotene, was calculed the IC50 and evaluated the antimicrobial activity.The results for focused microwave extraction generally indicated that the antioxidant activity (FRAP, ABTS and DPPH), total phenolics and total anthocyanins showed a positive linear trend in relation to the extraction temperature, with no significant difference between the solvent concentrations (60 and 80%). The IC50 and β-carotene showed the greatest inhibition at 60°C at solvent concentrations of 60% and 80%, respectively. The flavonoids showed no significant difference in terms of the extraction temperature or the concentration of solvent that was used. No antimicrobial activity was detected in the extracts in relation to the tested microorganisms. In the conventional method of extracting the best extraction conditions for phenolic compounds, flavonoids and anthocyanin employed 60% solvent, 60 minutes at 40ºC; however, the anthocyanins did not suffer any influence from time and temperature. The best results for the antioxidant activity using the DPPH and FRAP methods were obtained with 60% solvent, 30 minutes at 30ºC, and the DPPH was not influenced by temperature. Regarding ABTS+ the best results were reached with 60% solvent, 120 minutes, at 40ºC, while the β-carotene required 80% solvent at 40ºC, regardless of the time. The different extracts tested did not show antimicrobial activity. Ultrasound provided better phenolic extraction conditions, flavonoids and anthocyanins using 60% solvent, 20 minutes and 80 watts of power, and phenolic compounds not influenced by the power and flavonoids were not affected by the solvent. The antioxidant activity by DPPH and IC50 showed the best results com 60% solvent, 60 minutes and 80 W of power, the same conditions were found for β-carotene, but with 20 minutes of extraction. FRAP methodology is presented more efficient solvent 60%, 60 minutes and 220W power, whereas for the ABTS assay was 80% solvent and 80 W of power, independent of the extraction time. The extracts obtained through different methods of extraction showed no antimicrobial activity. However, the study confirms the antioxidant capacity of blueberries, which can be used as a functional ingredient or as a natural antioxidant in the preparation of food products.